Interferon gamma: friend or foe? - Wood, K; Feng, G; Wei, B; Sawitzki, B; Bushell, A (2007)
Interferon gamma (IFN-gamma) can elicit an inflammatory TH1-driven immune response but has also been found to be necessary for long-term allograft survival induced by costimulation blockade. Recently, we have found that regulatory T cells rapidly and transiently produce IFN-gamma creating a microenvironment that can influence the function of antigen presenting cells (APCs), T-cell proliferation and activation as well as T-cell effector mechanisms, thereby controlling immune responses locally. Moreover, addition of IFN-gamma to cocultures of T cells and APCs can drive the generation of T cells with regulatory activity. Thus, the influence of IFN-gamma on the immune response to a transplant is likely to be context dependent.